The Impact of Medical Records Management Training on the Quality of Medical Documentation in Healthcare Services - Wati, Lienda; -, Limisran (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2024)
Accurate and efficient medical documentation is key to providing quality healthcare. Effective medical records management can improve diagnostic accuracy, speed of service, and compliance with legal and ethical standards. This study aims to assess the impact of medical records management training on the quality of medical documentation in healthcare services, specifically at the PKU Muhammadiyah inpatient primary clinic. This research used a single-case study design involving staff at the clinic. Participants underwent a series of training sessions covering legal and ethical aspects, the use of medical records systems, and documentation and coding skills. The sample consisted of five healthcare workers. Assessments were conducted through pre- and post-tests measuring knowledge, as well as in-depth interviews with participants regarding the training. Data were analyzed using the Wilcoxon signed-rank test with a significance level of α≤0.05. The results showed a significant difference between pre- and post-training levels (p=0.03). Analysis of the in-depth interviews revealed increased participant confidence in managing medical records and perceptions of training utilization. Therefore, this study could significantly improve the quality of medical documentation.